Efficiency of Smallholder Cocoa Farmers in Malaysia: A DEA Approach - Wan Roshidah Fadzim; Mukhriz Izraf Azman Aziz; Ahmad Zafarullah Abdul Jalil (International Journal of Supply Chain Management, 2017)
Cocoa production in Malaysia faced several problems and challenges that lead to low productivity. The low productivity is evidenced from the continuous drop in cocoa productionsince 2001 despite efforts from governing bodies to boost output.This studyinvestigates this issue by looking into theproduction efficiencyamong small holder cocoa farmers in Malaysia.The technical efficiencies of cocoa farmers in Malaysia are estimated using data envelopment analysis. The study relies upon primary data gathered during the 2013 production season. Data are collected from a set of structured questionnaire administered on 323 smallholder cocoa farmers throughout Malaysia. Results ofthe analysis reveal that the mean efficiency score is 0.576. This indicates that many cocoa farmers in Malaysia are technically inefficient and this resulted into the low productivity in the Malaysian raw cocoa beans industry in recent years. This inefficiency is largely due to poor management and usage of inputs in the cocoa production.